Feasibility of Human Neural Stem Cell Transplantation for the Treatment of Acute Subdural Hematoma in a Rat Model: A Pilot Study - Yokobori, Shoji; Sasaki, Kazuma; Kanaya, Takahiro; Igarashi, Yutaka; Nakae, Ryuta; Onda, Hidetaka; Masuno, Tomohiko; Suda, Satoshi; Sowa, Kota; Nakajima, Masataka; Spurlock, Markus S.; Onn Chieng, Lee; et al. (Frontiers in Neurology, 2019)
Human neural stem cells (hNSCs) transplantation in several brain injury models has established their therapeutic potential. However, the feasibility of hNSCs transplantation is still not clear for acute subdural hematoma (ASDH) brain injury that needs external decompression. Thus, the aim of this pilot study was to test feasibility using a rat ASDH decompression model with two clinically relevant transplantation methods. Two different methods, in situ stereotactic injection and hNSC-embedded matrix seating on the brain surface, were attempted. Athymic rats were randomized to uninjured or ASDH groups (F344/NJcl-rnu/rnu, n = 7–10/group). Animals in injury group were subjected to ASDH, and received decompressive craniectomy and 1-week after decompression surgery were transplanted with green fluorescent protein (GFP)-transduced hNSCs using one of two approaches. Histopathological examinations at 4 and 8 weeks showed that the GFP-positive hNSCs survived in injured brain tissue, extended neurite-like projections resembling neural dendrites. The in situ transplantation group had greater engraftment of hNSCs than matrix embedding approach. Immunohistochemistry with doublecortin, NeuN, and GFAP at 8 weeks after transplantation showed that transplanted hNSCs remained as immature neurons and did not differentiate toward to glial cell lines. Motor function was assessed with rotarod, compared to control group (n = 10). The latency to fall from the rotarod in hNSC in situ transplanted rats was significantly higher than in control rats (median, 113 s in hNSC vs. 69 s in control, P = 0.02). This study first demonstrates the robust engraftment of in situ transplanted hNSCs in a clinically-relevant ASDH decompression rat model. Further preclinical studies with longer study duration are warranted to verify the effectiveness of hNSC transplantation in amelioration of TBI induced deficits.